Exploring the Didactic Principles of Vocational Teachers in Financial Education: An Interview Study - Nora Cechovsky (International Journal for Research in Vocational Education and Training)
Context: Financial literacy is an issue becoming increasingly important internationally. Many countries have already implemented a national strategy to improve the financial literacy of the people. In Austria, a national strategy for financial literacy and financial education was developed in 2021. One target group of this strategy are students of part-time vocational schools. These students work in a company and already earn their own money. They have to attend part-time vocational school alongside their work. The curriculum of these schools includes financial topics. Studies on teachers' views of financial literacy show that they mostly reduce it to personal money management. However, little is known about their underlying principles for teaching topics in the field of financial literacy. Therefore, this paper answers the following research questions: Which didactic principles are relevant for teachers of part-time vocational schools in Austria in financial education? Why are some didactic principles perceived as more relevant and why are others perceived as less relevant by the teachers?